2017
DOI: 10.5301/hipint.5000476
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Acetabular Morphology on Prediction of Proximal Femur Fractures Types in an Elderly Population

Abstract: The rate of trochanteric femur fractures is higher in patients with high acetabular index, whereas the rate of femoral neck fractures is higher in patients with increased hip axis length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Franken et al [ 20 ] also found that impingement-associated deformities of the hip may cause FNSF. Tokyay et al [ 21 ] pointed out that acetabular morphology can predict the types of proximal femoral fractures among elderly patients. NSA of trochanteric fracture was found to be less than that of the femoral neck fracture, but there was no statistically significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…Franken et al [ 20 ] also found that impingement-associated deformities of the hip may cause FNSF. Tokyay et al [ 21 ] pointed out that acetabular morphology can predict the types of proximal femoral fractures among elderly patients. NSA of trochanteric fracture was found to be less than that of the femoral neck fracture, but there was no statistically significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies comparing osteoporotic hip fractures regarding bone quality, age and morphology have been performed previously. Most of them assessed the proximal morphology as an important factor for determining the fracture type [9,18,19]. Cory et al investigated the fracture morphology of high shear angle vertical neck fractures in young adult patients under age of fifty years and vertical coronal fractured averaged 60 degrees and axial fracture obliquity averaged 24 degrees with deficiency in the posterior neck.…”
Section: Discussionmentioning
confidence: 99%
“…Franken et al [21] also found that impingement-associated deformities of the hip may cause femoral neck stress fractures. Tokyay et al [22] pointed out that acetabular morphology can predict the types of proximal femoral fractures among elderly patients. NSA of trochanteric fracture was found to less than the femoral neck fracture, but there was no statistically signi cant difference.…”
Section: Different Appearances Between Sfffh and Onfhmentioning
confidence: 99%